The Law of Minimum Vertical Dimension: Evidence for Improvement of Dental Occlusion - Silveira, Silvana; Valerio, Patricia; Machado Júnior, Almiro J. (European Journal of Dentistry, 2021)
The law of minimum vertical dimension (MVD) states that “when the mandible moves to reach the maximum intercuspal position, this always involves bringing the mandible and maxilla as close together as possible.” Therefore, after the first occlusal contact is made, the MIP will be reached through reduction of the vertical dimension. Our objective of this study, through an integrative review of the literature review, was to determine whether ignoring this law is a factor that contributes to malocclusion, temporomandibular joint dysfunction, and recurrences of functional orthodontic and orthopedic treatments.We conducted a search of the literature in five of the main electronic scientific databases. The following medical subject heading terms were used in our search: centric relation, dental occlusion, malocclusion, vertical dimension, and mastication. We cross-referenced the descriptors in the following four groups: centric relation and maximum intercuspation; occlusal plane and malocclusion; neuro-occlusal rehabilitation; and vertical dimension and unilateral chewing. From this, we selected 277 potentially eligible articles. Out of these, 209 were excluded in accordance with the exclusion criteria already described. Thus, 65 studies were included in the qualitative synthesis.The articles were also classified according to their impact factor and degree of recommendation, in conformity with the table of the Oxford Centre for Evidence-Based Medicine. The scientific interest in the scope of the articles was also assessed by using three charts developed according to year and country of publication and the percentage of publication. Unilateral chewing creates a vicious cycle of damage that leads to an ever-increasing masticatory deficiency. Most of the articles chosen for this review confirmed that noncompliance with law of MVD was a predisposing factor in cases of relapse, in functional orthodontic and orthopedic treatments, as well as a causal factor in malocclusion and in functional and morphological TMJ dysfunctions.
Keywords: centric relation; maximum intercuspation; occlusal plane; malocclusion; neuro-occlusal rehabilitation; vertical dimension; unilateral chewing